2002
DOI: 10.1029/2000rg000095
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Characterization of Global Sources of Atmospheric Soil Dust Identified With the Nimbus 7 Total Ozone Mapping Spectrometer (Toms) Absorbing Aerosol Product

Abstract: Citation: J. M. Prospero, P. Ginoux, O. Torres, S. E. Nicholson, and T. E. Gill, Environmental characterization of global sou7rces of atmospheric soil dust identified with the nimbus 7 total ozone mapping spectrometer (TOMS) absorbing aerosol product, Rev. Geophys.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

136
2,702
6
22

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,698 publications
(2,866 citation statements)
references
References 138 publications
136
2,702
6
22
Order By: Relevance
“…The TOMS project has produced the longest available global record of aerosol observations in terms of AI, and a number of studies have demonstrated its feasibility and success (e.g., Torres et al 1998;Chiappello et al 1999;Hsu et al 1999;Cakmur et al 2001;Prospero et al 2002;Duncan et al 2003). Monthly data on a 1.25°ϫ 1°grid are available on the TOMS Web site (http://toms.gsfc.nasa.gov/aerosols/aerosols_v8.html).…”
Section: Data and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The TOMS project has produced the longest available global record of aerosol observations in terms of AI, and a number of studies have demonstrated its feasibility and success (e.g., Torres et al 1998;Chiappello et al 1999;Hsu et al 1999;Cakmur et al 2001;Prospero et al 2002;Duncan et al 2003). Monthly data on a 1.25°ϫ 1°grid are available on the TOMS Web site (http://toms.gsfc.nasa.gov/aerosols/aerosols_v8.html).…”
Section: Data and Analysismentioning
confidence: 99%
“…The continuance of the westerly flow in spring across Afghanistan and Pakistan contributes to the piling up of aerosols in May. Indeed, during the premonsoon season, air masses carry the dry dust particles from the Middle East and the western Thar Desert (where dust activity peaks in late spring to early summer; see, e.g., Prospero et al 2002) to the IGP where they accumulate and interact with the large flux of regional pollutants from fossil fuels (typically invariant through the season) and biomass burning (predominant in spring; e.g., Dey et al 2004;Habib et al 2006).…”
Section: Toms Aerosol Index Variability Over the Indian Subcontinentmentioning
confidence: 99%
“…Many of the papers published to date that provide information on health-related particulate matter (PM) research have focussed on the impact of anthropogenically generated PM (such as PM generated by combustion engines) (Bousquet et al 2003;Bruce et al 2000;Ezzati 2005;Romieu et al 2002) while relatively little work has looked at the impact of naturally generated PM (such as PM emanating from dust storms). Winds from the nine principal desert sources transport large amounts of dust around the world (Prospero et al 2002;Tanaka and Chiba 2006). Overall, studies estimate that the global dust emission varies by a factor of slightly more than two, although extreme values from 1,018 Tg year −1 (Miller et al 2004) to 3,000 Tg year −1 (Tegen and Fung 1994) have been established over the last two decades (Engelstaedter et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The lake basins probably act as temporary sediment sinks during humid periods and then release sediment as the lakes dry out. At the present day, dry lake beds in the Sahara appear to be major sources of atmospheric mineral dust (Prospero et al 2002, Engelstaedter et al 2006) and in the case of the Bodélé Depression in Chad, which is the single largest source of atmospheric mineral dust on Earth (Washington et al 2003), wind erosion appears to have scoured out a deep basin (Washington et al 2006) providing a source of sand as well as dust.…”
Section: Discussionmentioning
confidence: 99%